Effect of nifedipine on atrioventricular conduction as compared with verapamil. Intracardiac electrophysiological study. Issue 2 (August 1979) - Rowland, E; Evans, T; Krikler, D
Abstract : Intravenous nifedipine, a powerful calcium antagonist, had no obvious effect on atrioventricular conduction when administered to 11 patients during routine intracardiac electrophysiological studies. Verapamil on the other hand showed potent antiarrhythmic properties, depressing atrioventricular nodal conduction. Nifedipine thus appears safe in patients with angina pectoris who have disorders of atrioventricular nodal conduction, and in those receiving beta-adrenergic blocking drugs. There appear to be differential effects on the slow inward channels of cardiac cells with different 'calcium antagonists'.